2022
DOI: 10.1111/jonm.13888
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of patients, and nursing and medical professionals as a result of digitalization of health and heart failure care

Abstract: The changing role of patients, and nursing and medical professionals as a result of digitalization of health and heart failure care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In addition, they can offer emotional support and reassurance to patients using digital devices, addressing any concerns or difficulties they may have. [ 11 ]…”
Section: Post-discharge Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they can offer emotional support and reassurance to patients using digital devices, addressing any concerns or difficulties they may have. [ 11 ]…”
Section: Post-discharge Disease Managementmentioning
confidence: 99%
“…Despite patients’ initial reluctance to embrace these changes, recent studies found many patients with HF and their caregivers recognise the benefits of the modern digital and artificial intelligence (AI) era. [ 11 , 12 ]…”
mentioning
confidence: 99%
“…[ 24 ]. Promoting the development, adoption and effective use of AI-based technologies (AITs) in health care has been identified as a key strategy to address the challenges related to both the complexity of managing the BPSD and limited resources [ 19 , 25 - 28 ]. Despite significant recent interest in the topic and the increasing number of technical devices on the market, little information is available on introducing AITs to help nurses attempting to detect BPSD as early as possible.…”
Section: Introductionmentioning
confidence: 99%